2010
DOI: 10.12681/mms.93
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-amylase inhibition kinetics by caulerpenyne

Abstract: Many algae have important secretions which are generally used for defensive purposes. These secretions have caught the attention of a number of researchers, as to whether or not these metabolites can be used in medical research. Among these metabolites, caulerpenyne (CYN) which is the main metabolite of the Caulerpa species, has had an important place in Caulerpa research since the beneficial effects related to its determined properties (such as cytotoxic, antiviral, antiproliferative and apoptotic) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It was presented in the previous reports that CYN, the main secondary metabolite of Caulerpa species, has some unique properties such as anticarcinogenic, antiproliferative, apoptotic and antiviral effects [16][17][18][19]. Moreover, the enzyme inhibitory effects of CYN towards some medically important enzymes like phospholipase A 2 , lipase, lipoxygenase and amylase have been shown by some researchers [21][22][23][24][25][26][27]. In the light of the knowledge above, the inhibitory effects of CYN on XOD enzyme activity were determined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was presented in the previous reports that CYN, the main secondary metabolite of Caulerpa species, has some unique properties such as anticarcinogenic, antiproliferative, apoptotic and antiviral effects [16][17][18][19]. Moreover, the enzyme inhibitory effects of CYN towards some medically important enzymes like phospholipase A 2 , lipase, lipoxygenase and amylase have been shown by some researchers [21][22][23][24][25][26][27]. In the light of the knowledge above, the inhibitory effects of CYN on XOD enzyme activity were determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the results of this study CYN can be classified as a good inhibitor for XOD and therefore, it can be recommended as a potential drug for XOD related diseases after in vivo studies. Unfortunately, CYN inhibits not only XOD but also phospholipase A 2 [21], lipoxygenase [22,23], pancreatic lipase [24,25] and alpha amylase [26,27]. Many drugs, which are currently used, act similarly and by reacting with different pathways they may have severe side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following up reports on the inhibitory activity of CYN ( 1 ) on microtubule protein polymerization, first synthetic CYN analogues in form of colchicine hybrids were generated, however with limited activity 3. CYN ( 1 ) itself is also active as inhibitor of telomerase,4 amylase,5 xanthine oxidase6 and plant lipoxygenases (LOs) 7. We reported that CYN ( 1 ) inhibits soybean LO with an IC 50 value of 5.1 μ M in an uncompetitive manner 7b.…”
Section: Methodsmentioning
confidence: 99%